The Islamic foundation of the theory of human relations and its educational applications - Al-Asiri, Ali Hassan (Journal of Educational and Psychological Sciences, 2024)
The current research aimed to root the theory of human relations and its principles in accordance with its connection with the Holy Quran, the Sunnah of the Prophet and the purposes of Islamic law, and to identify the most prominent applications of it in the educational field: That the Holy Quran and the Sunnah are an inexhaustible source and the best reference for the values and principles of modern management in its various fields, and that the heritage of the Islamic nation is full of evidence that indicates the greatness of the Islamic religion and its organization of human life in its dealings, plans, goals and objectives, and that Islamic administrative thought had the credit and precedence in establishing the principles of human relations and establishing the dimensions and contents of modern administrative theories in their various directions and objectives, and that the principles of modern human relations theory started from the results of behavioral science and the reflections and ideas of philosophers or unstable theories, while the principles of human relations Increasing care and attention to the Holy Qur’an and the Sunnah of the Prophet Muhammad, and the fixed legal principles they contain, which are considered an integrated and valid approach to life for all times and places, taking care to ground modern administrative theories in the light of the foundations and principles of Islamic thought, preserving the Islamic heritage and taking pride in it, and taking pride in the contributions of Muslim scholars in establishing and advancing sciences of various kinds, both ancient and modern.